Dietary profile of children born prematurely and alterations in the stomatognathic system from 24 to 36 months of corrected age (Research, Society and Development, 2021)
Objective: To verify whether the degree of prematurity influences the emergence of changes in the stomatognathic system and in the dietary profile of preterm infants between 24 and 36 months of corrected age. Methodology: Cross-sectional study, with 49 preterm infants with corrected age (24-36 months), divided into two groups: gestational age 32 weeks, evaluated variables: dietary profile, structures and functions of the stomatognathic system, feeding at discharge and alterations in the stomatognathic system. The variables between the two groups were compared using the chi-square test and the Monte Carlo method. Results: solid consistency diet predominated in both groups, alterations in the stomatognathic system were identified in both groups for tongue and palate sensitivity, tonus and posture of lips, tongue, cheeks and bite, with no statistical difference between them. Conclusion: There was no evidence of a relationship between the degree of prematurity/type of feeding and changes in the stomatognathic system, prematurity is a risk factor for the development of this system. As for the dietary profile at the age studied, no significant changes were detected, however, preterm infants with less than 32 weeks of gestation were more likely to use a bottle at hospital discharge. The structures and functions of the stomatognathic system must be evaluated by the speech therapist and whenever alterations are identified, it is essential that appropriate interventions are carried out.